Poject Based Learning: Cutting and Pasting to Increase Student Activity and Learning Outcomes in Fiqh Subjects - Rosendah Dwi Maulaya; Syahla Dhia Rafif; Rizka Alya Putri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
This study discusses the application of the Project Based Learning (PjBL) method in Fiqh learning at MI Nurussalam through cutting and pasting activities. This research is motivated by fiqh learning which has a monotonous and boring impression and low fiqh learning outcomes in grade 2 MI Nurussalam. The PjBL model involves active students, increasing students' motivation and critical thinking process. The purpose of this research is to increase the activeness of students and their learning outcomes. The research was conducted through a classroom action research approach with two cycles. The second cycle is a cycle of improvement from the reflection of the first cycle. Learning outcomes are evaluated through observation sheets. Learning outcomes and student activity increased from the first cycle to the second cycle, learning became more interactive, and the target of completeness of learning outcomes was achieved in the second cycle. Therefore, it can be concluded that the PjBL model is proven to be able to increase the activeness and learning outcomes of students at MI Nurussalam Mantingan.